1991
DOI: 10.1002/1097-0142(19910115)67:2<536::aid-cncr2820670236>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Black tobacco, maté, and bladder cancer. A case–control study from uruguay

Abstract: A case-control study of bladder cancer involving interviews with 111 incident cases and 222 controls was carried out in Montevideo, Uruguay. The analysis was conducted separately for each sex. Point estimates of relative risk associated with smoking variables, ingestion of infusions of the herb Ilex paraguariensis (maté), and selected dietary items were obtained by stratified and logistic regression analysis. Among men, smokers of black tobacco showed a relative risk (RR) 2.7 higher than blond tobacco smokers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 11 publications
0
33
1
1
Order By: Relevance
“…However, risk for bladder cancer was only 40% higher for smokers of black tobacco compared with smokers of blond tobacco, and this elevation was not statistically significant. Our findings suggest that risk associated with black tobacco compared with blond tobacco may not be as high as reported in previous studies, which have suggested that smokers of black tobacco have one and one-half to three times the risk of smokers of blond tobacco (2,6,(8)(9)(10)(11). In an earlier case-control study conducted in Spain (including the region of Barcelona), Lopez-Abente et al (5) reported little to no difference in bladder cancer risk associated with tobacco type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, risk for bladder cancer was only 40% higher for smokers of black tobacco compared with smokers of blond tobacco, and this elevation was not statistically significant. Our findings suggest that risk associated with black tobacco compared with blond tobacco may not be as high as reported in previous studies, which have suggested that smokers of black tobacco have one and one-half to three times the risk of smokers of blond tobacco (2,6,(8)(9)(10)(11). In an earlier case-control study conducted in Spain (including the region of Barcelona), Lopez-Abente et al (5) reported little to no difference in bladder cancer risk associated with tobacco type.…”
Section: Discussionmentioning
confidence: 99%
“…Bladder cancer risk tends to be higher in countries where smoking air-cured, or black, tobacco is more common. At least five studies in Spain, Italy, France, Uruguay, and Argentina have found higher risk among smokers of black tobacco compared with that among smokers of blond tobacco (2,6,8,9,11).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, DMBA, like BaP, is also an indirect-acting carcinogen, requiring metabolic activation to yield its ultimate carcinogenic form (Badal and Delgada, 2014), in particular an oxidation by CYP enzymes (Szaefer et al, 2014). Unlike the hot temperature of the infusion -accepted as a risk factor for cancers of the upper aerodigestive tract (De Stefani et al, 1988;1990;Lubin et al, 2014)-, the quoted components could be partially responsible of the association of 'mate' with cancer in organs which have no direct contact with the beverage: lung (De Stefani et al, 1996), bladder (De Stefani et al, 1991;2007), kidney (De Stefani et al, 1998b), prostate (De Stefani et al, 2011b) and also cervix uteri (De Stefani et al, 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…local studies about 'mate' (a hot infusion made from the herb ilex paraguariensis, which is a staple nonalcoholic beverage in temperate South America) and its role on cancer were mainly focused on the upper aerodigestive sites (Vassallo et al, 1985;De Stefani et al, 1988;1990;Castellague et al, 2000;Sewram et al, 2003;Ronco et al, 2004;Deneo-Pellegrini et al, 2013;Lubin et al, 2014), usually showing positive associations with these tumors.…”
mentioning
confidence: 99%
“…Although this approach facilitated data pooling, it is not possible to use the summary estimate to establish an exposure threshold for identifying individuals with elevated cancer risk. In addition, the authors noted that one of studies 7 introduced substantial heterogeneity to the meta-analysis. As such, they reported that the I 2 statistic, which describes the percentage of variation across studies that is due to heterogeneity rather than chance, was 0% before the study was added and went up to 67% after its addition.…”
Section: Summary Review/oral Cancermentioning
confidence: 99%